The impact of peak aerobic capacity on the performance of elite ski racers aged 18 to 20 in competitions at different distances - Golovachev A.I. ,; Kolykhmatov V.I. ,; Shirokova S.V. ,; Grushin A.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the impact of indicators of peak aerobic capacity in elite ski racers aged 18-20 on their performance in key races at different distances during the 2023-2024 ski racing season. Methods and structure of the study. The research project encompassed 11 athletes, aged between 18 and 20, who were experts in different sports. They had achieved the rank of CMS or MS. The study focused on their maximum aerobic capacity, evaluating their overall physical performance, strength, and the efficiency of their oxidative and lactic acid energy systems. Results and conclusions. It was discovered that the success of performances at goal-oriented events in cross-country skiing is largely determined by the extent to which the absolute and relative (related to the physical effort exerted) level of maximum oxygen consumption is developed, as well as the intensity of the lactic acid energy system's functioning, which contributes to the overall energy capacity required for muscular activity.